Pregabalin-associated adverse drug reactions - Fahad S. Alshehri; Ahmed M. Ashour; Nasser M. Alorfi; Abdullah S. Alshehri; Mahdi K. Almahdi; Fahad Mohammad Almowallad (Medicine, 2026)
Pregabalin is widely used for neuropathic pain, epilepsy, and anxiety disorders but has become increasingly associated with misuse and dependence. Understanding its global safety profile is essential to support pharmacovigilance and toxicovigilance efforts. This study aimed to characterize the pharmacological and toxicological patterns of pregabalin-related adverse drug reactions (ADRs) reported worldwide, with emphasis on neuropsychiatric toxicity, misuse, and social consequences. A retrospective, descriptive analysis was performed using the World Health Organization-VigiAccess database. All pregabalin-related ADRs reported up to October 2025 were extracted and categorized according to the Medical Dictionary for Regulatory Activities. Frequencies and percentages were calculated across System Organ Classes and Preferred Terms. Data were summarized descriptively to identify trends in demographic distribution, pharmacological effects, and misuse-related signals. A total of 164,223 ADRs were identified. The most frequent System Organ Classes were general disorders and administration-site conditions (21%), nervous system disorders (18%), psychiatric disorders (9%), and injury, poisoning, and procedural complications (8%). Adults aged 18 to 64 years accounted for most reports, with a slight female predominance and highest reporting from the Americas and Europe. Neuropsychiatric ADRs such as dizziness, somnolence, ataxia, euphoria, and aggression were common. Importantly, 3835 reports (≈1%) under social circumstances included explicit terms related to misuse and dependence, notably drug abuser (n = 42), drug diversion (n = 29), substance abuser (n = 12), and prescription form tampering (n = 36) – as well as functional impairments such as impaired driving ability (n = 710) and impaired work ability (n = 585). Pregabalin demonstrates a pharmacological and toxicological profile by central nervous system and psychiatric effects, with emerging global signals of misuse, dependence, and behavioral toxicity. These findings highlight the need for strengthened prescription monitoring, patient education, and integrated pharmacovigilance–toxicovigilance systems to reduce pregabalin-related public health risks while maintaining its therapeutic utility.